The Treatment of the Architectural Unit above Openings of the Mamluk and Ottoman Facades in Cairo - Saad Abdel Naby, Heba Mahmoud (Journal of Islamic Architecture, 2014)
The facades of the Mamluk buildings have a common characteristic feature which is the use of lintels, nafis and relieving arches above doors and windows. The three elements together formed a unit with an important architectural function on the façades. This unit was also treated as a focal point of the façade. Therefore, it was richly decorated with floral and geometric decorations and was usually made of colored marble, joggles voussoirs or carved stones. As a result, that unit attracted the attention of pedestrians and added to the beauty of the façade. During the Ottoman period the same unit was used on facades, however, due to financial and political reasons, the materials used differed and the decorations became modest. Nonetheless, the decoration of the lintel, nafis and relieving arch managed to mark the Ottoman facades with a different identity.